Fiddler on the roof - Jewison, Norman 1926- (Metro-Goldwyn-Mayer Studios and Norman Jewison, 1971)
Tevye is a poor Jewish milkman with five unmarried daughters to support in a village in Czarist Russia. With a sharp tongued wife at home and growing anti-Semitism in the village, Tevye talks to God about his troubles. His people's traditions keep him strong when his existence is as precariously balanced as a fiddler on the roof.